Navigating whiteness: affective relational intensities of non-clinical psychosocial support by and for culturally and linguistically diverse people - Mescouto, Karime; Olson, Rebecca E.; Plage, Stefanie; Zulfiqar, Asma; Setchell, Jenny; Dune, Tinashe; Suleman, Sameera; Cummins, Drew; Prasad-Ildes, Rita; Costa, Nathalia (Frontiers in Sociology, 2024)
Mental health is political, with intersecting economic, cultural, racialized, and affective dimensions making up the care assemblage, signalling how care is conceptualised and who is deserving of care. In this article, we examine emotions circulating in a non-clinical psychosocial support program for culturally and linguistically diverse people experiencing mental ill-health, foregrounding the relations between culture, race, economy, and assumptions underpinning understandings of care. The mental health program under study offers psychosocial support for culturally and linguistically diverse people to manage life challenges and mental ill-health exacerbated by navigating the complexities of Australia’s health and social care systems. We draw on interviews with clients, staff, and providers of intersecting services, employing Ahmed’s concept of affective economies and Savreemootoo’s concept of navigating whiteness to examine the care assemblage within interview transcripts. We provide insight into affective intensities such as hate, anger, and indifference embedded in white Anglo-centric services, positioning culturally and linguistically diverse people on the margins of care. Non-clinical psychosocial support programs can counter such affective intensities by training and employing multicultural peer support workers—people with lived experience—prioritising relational and place-based approaches to care and supporting and providing clients with relevant skills to navigate an Anglo-centric care system. However, this support is filled with affective tensions: (com)passion, frustration and fatigue circulate and clash due to the scarcity of resources, further signalling what type of care (and with/for whom) is prioritised within Australian relations of care.